Exploring the Role of Renewable Energy Technologies in Mitigating Energy Poverty in Sub-Saharan Africa - Chizema, Darlington; Mabugu, Ramos E.; Meniago, Christelle (International Journal of Energy Economics and Policy, 2025)
This study examines the effect of renewable energy consumption on energy poverty across 43 Sub-Saharan African countries from 2002 to 2021. Using a dynamic panel data approach and a two-step System GMM estimator, it addresses endogeneity concerns in energy poverty analysis. Results show energy poverty is persistent, reflecting deep institutional and infrastructural challenges. While renewable energy consumption is positively associated with energy poverty, the modest impact suggests current investments are concentrated in urban or grid-connected areas, with limited benefits for rural populations. This highlights the need for inclusive, decentralized energy strategies. Human capital emerges as a key factor in alleviating energy poverty, emphasizing the importance of integrating energy access with education and health initiatives. Conversely, GDP per capita, institutional quality, and population density show no significant effects, challenging assumptions that economic growth alone can resolve energy deprivation. The lack of a declining trend in energy poverty underscores the urgency for targeted, long-term interventions. The study advocates pro-poor energy policies, innovative financing, and multi-sectoral approaches linking energy access to broader development goals to advance Sustainable Development Goal 7 (SDG 7). Future research should explore subnational disparities and the varied impacts of renewable technologies to inform context-specific solutions.